THE ADDITION EFFECT OF (NaOH AND KOH) TO THE BIOGAS PURIFICATION - Yuninda Fahmayanti; Ahmad Abtokhi (Jurnal Neutrino: Jurnal Fisika dan Aplikasinya)
Biogas is a gas produced by the decomposition of organic materials involving microorganisms in the anaerobic state. The research focused on obtaining good quality biogas through NaOH and KOH purification by reducing H2S and CO2 levels. The purification of biogass proceeded in a variation of absorbent concentrations 0,05M, 0,1M, 0,15M  NaOH and KOH solution.  Gas chromatography chose for biogas characterization. Based on TCD detector in gas chromatography, it represented concentration area in percentage (%). The content of biogas for control was 2.14% CO2 and 0% H2S. The Addition of 0.05; 0,1M; 0,15M NaOH produced  1,57%, 1,56% and 2,98% CO2 respectively. Moreover, the addition of 0.05 M; 0,1M; 0,15M KOH yielded 0.81%, 0,30% and 1,03% CO2. The highest of the burning calories was the NaOH 0,15M amount of 66,528 kcal and the lowest of the burning calories was the 0,1M KOH amount of 38,976 kcal.